2021
DOI: 10.2196/27877
|View full text |Cite
|
Sign up to set email alerts
|

Best Practices for Integrating Medical Students Into Telehealth Visits

Abstract: Telehealth has become an increasingly important part of health care delivery, with a dramatic rise in telehealth visits during the COVID-19 pandemic. Telehealth visits will continue to be a part of care delivery after the pandemic subsides, and it is important that medical students receive training in telehealth skills to meet emerging telehealth competencies. This paper describes strategies for successfully integrating medical students into telehealth visits in the ambulatory setting based on existing literat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 41 publications
2
11
0
Order By: Relevance
“…Our study demonstrates that trainees were highly appreciative of direct observation and receiving real-time feedback from their supervising attending, as well as of pre- and post-visit case discussions, and recommended that these strategies be utilized for future telehealth visits. This is consistent with recent literature and is reflected in several publications [ 19 ••, 21 ••, 22 , 23 ]. Our findings additionally related concern from some trainees regarding technological difficulties and challenges with internet connection, which aligns with recent research demonstrating that connection quality is strongly linked to practitioner’s enjoyment of telehealth visits [ 24 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our study demonstrates that trainees were highly appreciative of direct observation and receiving real-time feedback from their supervising attending, as well as of pre- and post-visit case discussions, and recommended that these strategies be utilized for future telehealth visits. This is consistent with recent literature and is reflected in several publications [ 19 ••, 21 ••, 22 , 23 ]. Our findings additionally related concern from some trainees regarding technological difficulties and challenges with internet connection, which aligns with recent research demonstrating that connection quality is strongly linked to practitioner’s enjoyment of telehealth visits [ 24 ].…”
Section: Discussionsupporting
confidence: 93%
“…Along with our recent work [ 17 ], this is the first study, to our knowledge, to evaluate the effects of telehealth in clinical education in Adolescent Medicine. Similar to prior studies, we found trainees had concerns about inability to observe pertinent physical exam skills during telehealth encounters, reported occasional discomfort holding difficult conversations virtually, and sometimes found it difficult to fit into the conversation [ 18 , 19 ••]. Over the course of the past year, several articles outlining best practices and standardized visit structures for telehealth precepting have been published and offer some solutions to the challenges this format poses.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Telehealth demands a distinctive skill-set compared to conventional face-to-face consultations, in which medical students will need to gain skills and demonstrate competence in the future [ 78 , 79 ]. Some recent studies describe the development of a telehealth curriculum [ 80 , 81 ] and we prompt further primary research to establish the optimum approach for telehealth curriculum delivery and examination of telehealth skills of medical students.…”
Section: Discussionmentioning
confidence: 99%
“…Questions were developed using the AAMC's proposed competencies with telehealth. 10 Committee members piloted the survey questions with each other and the STFM Task Force members. The final instrument asked questions regarding in which years of medical school telehealth was taught pre-and-during COVID; number of hours of formal didactic curriculum dedicated to teaching telehealth pre-and-during COVID; opportunities medical students have to learn about telehealth; how COVID has changed the percent of visits students participate in telehealth; what types of simulated visits are happening at your medical school; and what are the key barriers to teaching telehealth as part of the medical school curriculum.…”
Section: Methodsmentioning
confidence: 99%